An assessment of the SBIR program at the National Science Foundation - Wessner, Charles W. (Online access: NCBI NCBI Bookshelf., 2008)
The study sought to understand operational challenges and to measure program effectiveness, including the quality of the research projects being conducted under the SBIR program, the challenges and achievements in commercialization of the research, and the program's contribution to accomplishing agency missions.